Peran Jam'iyyah Pusat Ar-Rohmah dalam Pembentukan Potensi Diri Santri di Pondok Pesantren Haji Ya’qub Lirboyo Kediri - Arjun Masruri (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
This article discusses the important role played by Jam'iyyah Pusat Ar-Rohmah in forming the self-potential of students. Jam'iyyah here can be interpreted as a social organization within the Haji Ya'qub Lirboyo Islamic boarding school which provides various extracurricular activities, guidance and social support to the students. This research aims to highlight Jam'iyyah's contribution in shaping the intellectual, moral and social potential of santri. Therefore, this research seeks to explore the role of Jam'iyyah Pusat Ar-Rohmah, as an organization at the Haji Ya'qub Islamic Boarding School in shaping the self-potential of students. From the description above, the research focus is as follows: 1). How does Jam'iyyah Ar-Rohmah Center shape the personal qualities of students at the Ya'qub Lirboyo Haji Islamic Boarding School, Kediri City? 2). What are the inhibiting and supporting factors in forming the self-potential of students at the Haji Ya'qub Islamic Boarding School. The research methods used were interviews, observation and literature study. The results of research (1) show that Jam'iyyah Center Ar-Rohmah plays a role in developing various aspects of students' personal potential, including personality, religious knowledge and social skills. (2) This article also describes several factors that influence the effectiveness of the role of Jam'iyyah Pusat Ar-Rohmah in forming the self-potential of students and the inhibiting factors. This research shows that the role of Jam'iyyah Ar-Rohmah Center is not only to support the development of santri, but also to be an integral part of Islamic boarding school education.